2012
DOI: 10.1097/mao.0b013e318268d4e0
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Evaluation of Soft Tissue Integration of Experimental Abutments for Bone Anchored Hearing Implants Using Surgery Without Soft Tissue Reduction

Abstract: Objective: The protocol for bone-anchored hearing implants (e.g., Baha A ) surgery involves reduction of soft tissues around the abutment to minimize the risk of skin-related complications. It is hypothesized that good soft tissue outcomes may be achieved without performing skin reduction if improved abutment designs and/or materials are used that provide enhanced integration with surrounding soft tissues. The aim of the study was to investigate soft tissue response to different abutment designs/materials. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
1
47
1
Order By: Relevance
“…Subsequently, Hulcrantz 12 showed that no soft tissue reduction did not compromise implant stability or surrounding soft tissue status following BAHA implantation. This has been further validated by the histologic findings of Larrson et al, 13 who found limited or no signs of inflammation in the soft tissue surrounding the abutment when no soft tissue reduction was performed with BAHA implantation in sheep. Our technique takes a further step with even less manipulation of the soft tissue surrounding the implant.…”
Section: Discussionmentioning
confidence: 73%
“…Subsequently, Hulcrantz 12 showed that no soft tissue reduction did not compromise implant stability or surrounding soft tissue status following BAHA implantation. This has been further validated by the histologic findings of Larrson et al, 13 who found limited or no signs of inflammation in the soft tissue surrounding the abutment when no soft tissue reduction was performed with BAHA implantation in sheep. Our technique takes a further step with even less manipulation of the soft tissue surrounding the implant.…”
Section: Discussionmentioning
confidence: 73%
“…3 This surgical technique is based on a new generation of abutments, whose main difference is their greater length in order to adapt to the thickness of the patient's skin and better integration with the subcutaneous tissue. 8 Although there are still a few published articles on this new technique, those that there are, describe very good results. In their series, Husseman et al 9 found 34 cases of BAHA where only 15% presented a reaction which was higher than a Holger's grade 2, but they do not compare with a reference group.…”
Section: Discussionmentioning
confidence: 93%
“…Additionally, the skin thinning and hypertrophic scar tissue could reduce blood transport, thus potentially hampering the local immunological responses of importance in the healing procedure and in peri-implant infections (21). Recent studies indicate that the omission of skin thinning may be preferable to any reduction of the subcutis, as it does not augment skin problems clinically or histologically and it allows for a better aesthetic outcome (1,4,6,22). These results were reinforced in the current study, as no increased rate of skin-related problems was observed in the test group 5 years after implantation.…”
Section: Discussionmentioning
confidence: 98%